Integrating Cloud Technology in Language Learning: Development of a Basic English Grammar E-Book - Jaya, Hariswan Putera; Pitaloka, Novalingga; Zuraida; Anggraini, Hesty Wahyuni (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aimed to investigate the development of a cloud-integrated e-book intended to enhance Basic English Grammar training for first-semester students in the English Education Program. A Research and Development (R&D) methodology employing the ADDIE model was utilized, which includes analysis, design, development, implementation, and evaluation. Data were collected using pre-test, post-test, interviews, and questionnaires. The results indicated a notable enhancement in student performance, with an average increase of 16.573 points (from M = 61.37 to M = 77.95) and a p-value of 0.000, substantiating the efficacy of the intervention. Furthermore, qualitative feedback revealed a significant demand for modern and interactive materials, highlighting the imperative to include technology into educational tools. The cloud-based e-book seeks to deliver accessible, engaging, and adaptable grammar instruction, facilitating ongoing updating and real-time collaboration. This unique technology solves the constraints of traditional teaching materials and supports consistent learning results, boosting students' understanding of English grammar and enhancing their overall educational experience.